Macroeconomic Accounting and Analysis in Transition Economies - Ouanes, Abdessatar (International Monetary Fund, 1997)
This book, by Abdessatar Ouanes and Subhash Thakur presents the principal elements of macroeconomic accounting and analysis for the real, fiscal, monetary, and external sectors of a transition economy, using Poland as a case study. Background information, exercises, and issues for discussion are also provided.